Aplicación de una auditoría ambiental en la estación de servicios Primax mejía ubicada en la provincia de Pichincha, cantón Mejía parroquia Machachi del 01 de enero al 31 de diciembre del 2012 - Cruz Naula, Katherine Marisol (2014)
This investigative work has as main objectives to evaluate the performance of environmental rules and give verified evidence, that the environmental audit was made at the “Primax Mejia” gas station from Machachi parish, detailing the novelties found in the examination of the six elements that have been audited. To obtain actual information, it was used investigational techniques such as: interview and survey, through the concrete obtained results about the situation of the gas station with relation to the fulfilment of the environmental rules. This research is helpful to the administration and management, since it was possible to evidence inconvenients related to the fulfilment of the environmental rules, which are showed in the items about control and the final report in which contains the conclusions and recommendations.